Factors influencing the consumers’ purchase intentions toward Organic food - Nimra Nasir (International Journal of Experiential Learning & Case Studies)
The fundamental drivers of sustainable consumer behavior are consumption ideals. This study examines the relationship between consumption values (functional, social, economic, and emotional), attitude toward buying, perceived behavioral control, and the intention to buy organic food by incorporating the theory of consumption approach. With a Google form survey, the data was collected from 156 organic food buyers in Karachi (Pakistan) because of limited resources. Using the PLS-SEM method, we discover that consumers’ intentions to buy organic food are significantly positively influenced by economic value, emotional value, social value, and functional value quality. The structural relationship between consumption values and the intention to buy organic food is further found to be significantly mediated by attitude toward purchasing. In contrast, the relationship between attitude toward purchasing and the intention to buy organic food was moderated by perceived behavioral control. According to our findings, promoting treatments that address attitudes toward purchases is a potential method to encourage persistent purchase intentions. These findings significantly impact how the organic food business develops based on consumer preferences.